Projeto e desenvolvimento de um retificador híbrido monofásico bidirecional com compensação série no barramento CC para aplicações em microrredes CC - Barbosa, Vítor Fonseca (2020)
This work presents a new topology of a Single-Phase Hybrid Bidirectional Rectifier with series voltage compensation on the DC bus and a decentralized control proposal for applications in DC microgrids. The structure in question operates connected to the grid in two distinct modes: rectification and inversion, defined based on the amount of energy available from distributed generation sources, in addition to an interface with the grid with a high power factor and low harmonic distortion of the input current input within the limits established by the IEC 61000 3- 2 standard in the rectification and IEEE 1547 in the injection of current into the grid. In order to evaluate the functionality of the structure, the aid of the PSIM® software became indispensable to consolidate in practice a 400W prototype controlled by a Digital Signal Processor. Finally, the viability of this structure is proven to control DC microgrids, since its advantages include the use of few sensors, robustness and control stability.